Tindak Tutur Ilokusi Ujaran Kebencian Terhadap Penyanyi Pinkan Mambo Di Media Sosial Instagram - Musa’adah, Lailatul; Shofianti, Zulya; Suryani, Yunita (STAI Denpasar Bali, 2023)
Hate speech, often referred to as hate speech, is an act of communication carried out by an individual or a group that can be in the form of provocation, humiliation, or blasphemy against individuals or groups on various occasions and conditions, such as skin color, race, physical imperfection, gender, sexual orientation, religion, and many others. Hate Speech itself has never escaped society's use of social media technology, especially Instagram. Instagram is a special application on a smartphone that is used for social media. These applications are almost identical to Twitter in terms of functionality but differ in how they are used to share information. One of the differences lies in the app's ability to take photos and share them with other users.